PENGGUNAAN MEDIA BUKU SAKU UNTUK MENINGKATKAN KETERAMPILAN MENULIS SISWA KELAS III DI SD NEGERI 3 JUNGUTBATU - Ayu Yuliantari, Komang; Sudirman, Nyoman; Nada Kusuma, I Komang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The writing skills of third-grade students of SD Negeri 3 Jungutbatu are still low, especially in the use of capital letters and punctuation, sentence structure according to the SPOK structure, and the development of ideas into simple paragraphs. This study aims to improve students' writing skills through the use of pocket books. This study is a Classroom Action Research (CAR) which was carried out in two cycles with the stages of planning, implementation, observation, and reflection. The research subjects were 14 students. Data were collected through writing skills tests and observations, then analyzed descriptively quantitatively and qualitatively. The results showed that the average student writing skills increased from 59.64 in the initial reflection to 61.96 in Cycle I and 80.18 in Cycle II. The percentage of classical learning completion also increased from 14.28% to 35.71%, then reached 92.86% in Cycle II. Improvements occurred in all indicators of writing skills, including the use of capital letters and punctuation, sentence structure (SPOK), neatness of writing, appropriateness of the theme, and the use of one's own language. Thus, pocket book media effectively improves the writing skills of grade III students at SD Negeri 3 Jungutbatu.